Smart home technology to support engagement in everyday activities while ageing: A focus group study with current and future generations of older adults. - William Son Galanza; Jens Offerman; Sofi Fristedt; Susanne Iwarsson; Nebojsa Malesevic; Steven M Schmidt (PLoS ONE)
Despite the potential of smart home technologies (SHT) to support everyday activities, the implementation rate of such technology in the homes of older adults remains low. The overall aim of this study was to explore factors involved in the decision-making process in adopting SHT among current and future generations of older adults. We also aimed to identify and understand barriers and facilitators that can better support older adults' engagement in everyday activities. Focus group discussions were used to explore the perspectives of people from diverse age groups (30-39, 50-59, and 70-79-year-olds). Three focus groups met twice at a lab designed as a two-room home equipped with SHT. Our findings revealed that the participants' decision-making process for adopting SHT involved designs that must be adapted to the changing physical abilities and diverse needs of users. Some conditions, such as ideas for re-invention, were identified after the integration of SHT. Concerns about reliability, complicated interfaces, and value to the user influenced the decision to adopt SHT, highlighting the importance of these factors for successful implementation. Some participants did not fully understand what SHT is nor perceive its benefits, but they expressed a desire to acquire the skills and knowledge to operate SHT. Furthermore, participants desired SHT that can support an active lifestyle. The perceived advantages of SHT include enhancing the sense of security and safety, which can facilitate engagement in everyday activity. Some participants experienced a positive impact on quality of life, related to comfortable living with the implementation of SHT. Adults across age groups perceive that SHT can enhance engagement in everyday activity and the sense of safety and security. However, it is essential to identify solutions for better usability. More collaborative efforts involving diverse stakeholders are vital to bridge the disconnect between SHT design and users' needs and preferences.